(untitled) (KULT_online, 2014)
How can average individual citizens take responsibility for past crimes against humanity? How can they take active part in developing solutions without participating in the same systems of violence they struggle against? This book takes an interdisciplinary look at questions of responsible selfhood, and places its inspection on Germany during the Third Reich. Combining backgrounds in history, literary criticism, philosophy and theology, the four authors investigate the role that myths, lies, non-conformity and irony play in the construction of the “self”. By discussing the ambiguity behind these concepts, as well as the inherent instability of the self, the authors present strategies for developing responsible individuals who are happy to bear the burden of history.